2019
DOI: 10.2151/sola.2019-023
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Global Warming on Extreme Rainfall of a Slow-Moving Typhoon: A Case Study for Typhoon Talas (2011)

Abstract: This study investigated the impacts of global warming on extreme rainfall produced by a slow-moving typhoon by conducting pseudo-global warming (PGW) experiments. We examined Typhoon Talas (2011) that caused long-lasting heavy rainfall exceeding 2000 mm over the Kii Peninsula. The experiments successfully captured the track and translation speed of the actual typhoon, which enabled to quantitatively assess the climate change impacts. The PGW experiments indicated that the extreme rainfall is intensified in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 30 publications
1
16
0
Order By: Relevance
“…A pseudo-global warming (PGW) experiment is one method of evaluating the impacts of global warming in the future climate on past TCs. This approach has been applied to typhoons hitting Japan such as Typhoons Vera (1959), Songda (2004), Talas (2011), Canthu (2016, and Lionrock (2016) (Ito et al 2016;Takemi et al 2016;Kanada et al 2017aKanada et al , 2017bNayak et al 2019;Takemi 2019). These studies indicated that extreme typhoons got stronger under the future global warming scenario.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A pseudo-global warming (PGW) experiment is one method of evaluating the impacts of global warming in the future climate on past TCs. This approach has been applied to typhoons hitting Japan such as Typhoons Vera (1959), Songda (2004), Talas (2011), Canthu (2016, and Lionrock (2016) (Ito et al 2016;Takemi et al 2016;Kanada et al 2017aKanada et al , 2017bNayak et al 2019;Takemi 2019). These studies indicated that extreme typhoons got stronger under the future global warming scenario.…”
Section: Introductionmentioning
confidence: 99%
“…These studies indicated that extreme typhoons got stronger under the future global warming scenario. Takemi (2019) pointed out that increased precipitable water led to increased rainfall produced by Typhoon Talas (2011) despite the stabilized atmospheric Kawase et al, Impact of historical warming on Typhoon Hagibis (2019) 4 condition in the future climate; Takemi (2019) also indicated that global warming could enhance long-lasting heavy rainfall caused by slow-moving typhoons.…”
Section: Introductionmentioning
confidence: 99%
“…In this nudging technique, the maximum wavenumber and the nudging coefficient were chosen as 2 and 0.00028 s −1 , respectively. Note that the spectral nudging plays a critical role in better reproducing the tracks of tropical cyclones (Takemi et al 2016b;Takemi 2018a;Takemi 2019). Furthermore, a typhoon bogus scheme which prescribes a Rankine-type vortex was employed to initialize a typhoon vortex at the initial time of the time integration.…”
Section: Numerical Model and Experimental Designmentioning
confidence: 99%
“…The nonhydrostatic dynamics were set for all domains with Lambert conformal conic map projection and were integrated in time with a 30 s time step for the outermost domain. A spectral nudging technique was used on the horizontal wind components and geopotential in the x and y directions of the outer domains with wave number 5 to include synoptic‐scale influences (Cha et al ., 2011; Choi and Lee, 2016; Moon et al ., 2018; Takemi, 2019). Nudging coefficients of 2.8 × 10 −4 s −1 , which correspond to a roughly 1 hr time scale, and nudging‐layer heights from the 200 hPa level up to the model top were used.…”
Section: Numerical Experiments and Data Usedmentioning
confidence: 99%